Airborne Lidar Bathymetry - , Japan Coast Guard (The International Hydrographic Review, 2017)
The Hydrographic and Oceanographic Department of the Japan Coast Guard (JHOD) has been conducting airborne lidar bathymetry (ALB) for 14 years. Owing to ALB’s survey efficiency and high resolution, JHOD has applied the technique to various purposes such as, to say nothing of charting, recovery of tsunami-stricken harbors, surveillance for security, and research into volcanic activity. This note briefly describes the operation of the JHOD lidar system and outlines our typical outcomes.